2018
DOI: 10.1007/s00345-018-2269-8
|View full text |Cite
|
Sign up to set email alerts
|

Parental awareness of testicular torsion amongst Irish parents

Abstract: Education of this topic to the general Irish population and in particular to parents and young males is not established. Both knowledge of testicular torsion and awareness of the urgency in presentation are factors that determine parents promptness in seeking medical attention for their child in the setting of acute scrotal pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…British researchers ( 11 ) found that only 30% of their patients sought medical attention within 6 hours of symptoms (46% presented after 12 hours), and 2/3 of those were incognizant that the disease could cause organ loss. Similarly, American investigators ( 12 ) reported that only 1/3 of 479 parents surveyed in a Pediatric Urology clinic had some knowledge about the disease, and an Irish study ( 13 ) uncovered that although 56% of parents knew about the disease, just 1/3 were aware of the time frame available for treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…British researchers ( 11 ) found that only 30% of their patients sought medical attention within 6 hours of symptoms (46% presented after 12 hours), and 2/3 of those were incognizant that the disease could cause organ loss. Similarly, American investigators ( 12 ) reported that only 1/3 of 479 parents surveyed in a Pediatric Urology clinic had some knowledge about the disease, and an Irish study ( 13 ) uncovered that although 56% of parents knew about the disease, just 1/3 were aware of the time frame available for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…While the time interval between symptoms and first medical assessment, i.e. presentation delay, rests upon the patient’s awareness of the disease and medical care availability ( 11 - 13 ), delays from this first assessment until evaluation at the treating institution have been associated with the first examining physician’s clinical diagnosis and subsequent action, such as imaging studies orders and inter-hospital patient referral and transfer ( 14 - 16 ). This information, however, comes from economically advanced countries, and although one may postulate that similar associations should also be observed in emerging countries, region-specific data is necessary to ascertain not only the existence but also the magnitude of these associations.…”
Section: Introductionmentioning
confidence: 99%
“…Our results are consistent with those obtained in the Alyami et al study; it found that as the number of boys in the family increases, the parents' awareness of TT also increases [8]. Parents with only girls in the family will not directly be impacted, but if they were aware of it, they might share the knowledge with other parents who have boys in their family since several studies have demonstrated that parents who were aware of testicular torsion mostly learned about it via friends, relatives, and the internet, which stands as the most common source of knowledge [8][9][10][11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been published on parents' awareness of testicular torsion in Saudi Arabia and around the world [8][9][10][11][12]. However, no studies have been conducted in the western region of Saudi Arabia to address parental knowledge and awareness of TT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation